Mother's smoking and complex lung function of offspring in middle age: A cohort study from childhood. Issue 5 (11th March 2016) - Perret, Jennifer L.; Walters, Haydn; Johns, David; Gurrin, Lyle; Burgess, John; Lowe, Adrian; Thompson, Bruce; Markos, James; Morrison, Stephen; Thomas, Paul; McDonald, Christine; Wood‐Baker, Richard; et al.
Abstract: Background and objective: Existing evidence that supports maternal smoking to be a potential risk factor for chronic obstructive pulmonary disease (COPD) for adult offspring has barely been mentioned in major guideline documents, suggesting a need for more robust and consistent data. We aimed to examine whether such early life exposure can predispose to COPD in middle age, possibly through its interaction with personal smoking. Methods: The fifth‐decade follow‐up of the Tasmanian Longitudinal Health Study cohort, which was first studied in 1968 ( n = 8583), included a 2004 postal survey ( n = 5729 responses) and subsequent laboratory attendance ( n = 1389) for comprehensive lung function testing between 2006 and 2008. Multivariable linear and logistic regression models included sampling weights. Results: Post‐bronchodilator airflow obstruction (less than fifth percentile) was detected for 9.3% ( n = 123) of middle‐aged offspring. Its association with heavy maternal smoking (>20 cigarettes/day) during childhood was 2.7‐fold higher than for those without exposure (95% confidence interval [1.3, 5.7] P = 0.009). Maternal smoking per se approximately doubled the adverse effect of personal smoking on gas transfer factor ( z ‐score −0.46 [−0.6 to −0.3] vs −0.25 [−0.4 to −0.1], P [interaction] = 0.048) and was paradoxically associated with reduced residual volumes for non‐smokers. Conclusions: Heavy maternal smoking during childhood appears to predispose to spirometrically defined COPD. The interplay between maternal and personal smoking on gas transfer factor suggests that early life exposure increases an individual's susceptibility to adult smoking exposure. These findings provide further evidence to suggest that maternal smoking might be a risk factor for COPD and reinforce the public health message advocating smoking abstinence. Abstract : Heavy maternal smoking during childhood was associated with postbronchodilator airflow obstruction for middle‐aged offspring, and the exposure itself augmented the effects of personal smoking on gas transfer factor. This study suggests that early life exposure might increase an individual's susceptibility for chronic obstructive pulmonary disease, especially related to personal smoking in later life.